Bimetallic Ni-Pd synergism-mixed metal catalysis of the mizoroki-heck reaction and the suzuki-miyaura coupling of aryl bromides - Kashid, Abhijit A.; Patil, Dharmaraj J.; Mali, Ramling D.; Patil, Vijay P.; Neethu, T. V.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Catalysis Letters, 2021)
A combination of Pd and Ni complexes activated aryl bromides for the thermal Mizoroki-Heck reaction and Suzuki coupling giving high yields in short reaction times. A thermal redox mechanism probably occurs whereby Ni complex transfers electron and reduces the Pd (II) to Pd (0) which then takes the reactants through the standard protocol of oxidative-addition, migratory insertion and reductive elimination, typical for the Mizoroki-Heck reaction and the Suzuki coupling. [GRAPHICS] .
Keywords: Bimetallic catalysis; Mizoroki-Heck; Nickel complexes; Pd(OAc)2; Suzuki coupling

Bimetallic quantum dots (Cu-Pd, Ni-Pd) catalyzed reaction of bromo arenes with alkenes and aryl boronic acids - Raut, Pallavi K.; Meroliya, Heena K.; Dumbre, Swapnil R.; Patil, Vaishali N.; Solanki, Bhanupratap S.; Waghmode, Shobha A.; Iyer, Suresh (Indian Journal of Chemistry, 2023)
Bimetallic quantum dots (Cu-Pd and Ni-Pd) are active ligand-free catalysts for the alkenylation and arylation of aryl bromides. The catalysts are easy to synthesize by benign green protocols and characterized by various techniques. The bimetallic QD catalysts synthesized thus are superior to Pd(OAc)2 or other Pd NP catalysis of alkenylation reactions of aryl bromides with similar E-selectivity. The reaction of aryl bromide with aryl boronic acid is facile with high yields.
Keywords: Aryl bromides; Bimetallic QDs catalysis; Cu-Pd; Mizoroki-Heck; Ni-Pd; Suzuki coupling